ANALISIS PENGARUH VARIASI JARAK DAN TINGGI STIK SPRINKLER TERHADAP KINERJA IRIGASI PADA LUAS LAHAN TERBATAS - I Dewa Gede Jaya Negara; Syamsul Hidayat; I Wayan Yasa; Ni Luh Ayu Aprilianti (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
The conversion of agricultural land in urban areas has resulted in increasingly narrow agricultural land and many irrigation networks are not functioning. This has resulted in many isolated lands that cannot even be served by irrigation, so that the alternative source of agricultural water is local shallow ground well water. With the potential of water sources and limited land area, farming is expected to utilize water efficiently. Small sprinkler irrigation systems such as the 24D Netafim on the market, are expected to be an alternative in providing irrigation and for that it is necessary to test the ability of the irrigation system on the irrigation radius and its uniformity at a duration of 15 minutes. The test results showed that the irrigation uniformity was above 85% at the distance between sprinklers 4.5 m, 5 m and 5.5 m and 6 m with a stick height of 0.5 m and 0.75 m. For stick heights of 1.0 m and 1.25 m at the same sprinkler distance, the uniformity coefficient is less than 85%. While the optimal irrigation radius obtained at a sprinkler distance of 4.5 m, 5 m and 5.5 m is an average of 5.6 m.